Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1093/brain/aww310
|View full text |Cite
|
Sign up to set email alerts
|

Genetic inactivation of glutamate neurons in the rat sublaterodorsal tegmental nucleus recapitulates REM sleep behaviour disorder

Abstract: SEE SCHENCK AND MAHOWALD DOI101093/AWW329 FOR A SCIENTIFIC COMMENTARY ON THIS ARTICLE: Idiopathic REM sleep behaviour disorder is characterized by the enactment of violent dreams during paradoxical (REM) sleep in the absence of normal muscle atonia. Accumulating clinical and experimental data suggest that REM sleep behaviour disorder might be due to the neurodegeneration of glutamate neurons involved in paradoxical sleep and located within the pontine sublaterodorsal tegmental nucleus. The purpose of the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(56 citation statements)
references
References 48 publications
4
52
0
Order By: Relevance
“…Jouvet specifically found that lesions of this region in cats caused a perculiar state dissociation in which the animals appeared to ‘act out’ their dreams. Subsequent experimental work spanning several decades further refined the location of this ‘atonia generator’ to a region of the pons called the sublaterodorsal nucleus (SLD) in rodents (also termed the subcoeruleus region) [8,14,84–86] (Figure 3). …”
Section: Brain Circuitry Controlling Rem Sleepmentioning
confidence: 99%
See 2 more Smart Citations
“…Jouvet specifically found that lesions of this region in cats caused a perculiar state dissociation in which the animals appeared to ‘act out’ their dreams. Subsequent experimental work spanning several decades further refined the location of this ‘atonia generator’ to a region of the pons called the sublaterodorsal nucleus (SLD) in rodents (also termed the subcoeruleus region) [8,14,84–86] (Figure 3). …”
Section: Brain Circuitry Controlling Rem Sleepmentioning
confidence: 99%
“…Selective disruption of glutamatergic transmission of SLD and dorsally adjacent caudal laterodorsal tegmental (cLDT) neurons produces REM sleep without atonia. Interestingly, inactivation of these same neurons also reduced total time spent in REM sleep in mice [86,90]. Hence in addition to regulating REM sleep motor atonia, glutamatergic cLDT-SLD neurons also play a role in generating the forebrain features of REM sleep.…”
Section: Brain Circuitry Controlling Rem Sleepmentioning
confidence: 99%
See 1 more Smart Citation
“…) . In a recent study, a research group from Lyon demonstrated that genetic inactivation of glutamate neurons in the rat pontine sublaterodorsal tegmental nucleus was sufficient to cause loss of REM atonia . These findings mirror a human study using neuromelanin‐sensitive magnetic resonance imaging, in which reduced signal intensity in an equivalent region (the locus coeruleus/subcoeruleus complex) was observed in idiopathic RBD patients …”
Section: Parasomniasmentioning
confidence: 68%
“…In autopsy brains of PD patients who developed PD and dementia with Lewy bodies (DLB) preceded by idiopathic RBD, LBs were identified in the pedunculopontine tegmental nucleus (PPN), locus coeruleus/subcoeruleus complex, and gigantocellular reticular nucleus in medulla oblongata [46]. These regions are considered part of the neural circuit controlling atonia during REM sleep in animal experiments [6,47,48] and thus responsible for RBD. In this way the pathological progression of PD largely follows Braak's staging.…”
Section: Prodromal Symptoms Of Pd Patientsmentioning
confidence: 99%